Assessment of tidal energy resources in the Strait of Magellan in southern Chile (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The Strait of Magellan in the Chilean Patagonia (Lat: 53.5°S) connects the Atlantic and Pacific oceans through a narrow passage. Historic and current pressures from navigation, oil and coal industries combined with changes due to anthropogenic climate change and local population growth make the region both complex and relevant. A large tidal range on the Atlantic side of the strait produces very strong currents in the first and second narrows that have a significant potential for hydrokinetic energy. Maximum currents have been measured up to 5 m/s. With the goal of performing a detailed assessment of the marine energy potential of the strait, field measurements combined with an FVCOM numerical simulations are being used to assess the tidal potential and understand the complex coastal physics of the system. Field observations were carried out in short field campaigns in 2018 and 2019 to characterize the flow in one of the channel narrows. We deployed a moored ADCP for currents and turbulence characterization, measured salinity and temperature, sea-surface elevations with pressure sensors, and made velocity transects with a vessel-mounted ADCP. These characterizations will also help to inform the role of the flow through the Strait of Magellan on the continental shelf.  The field data we collected is critical to understand the factors that control the dynamics of the flow in this section of the channel, and understand its marine energy potential. Measured velocities are being used to validate an FVCOM numerical model which will expand our spatially and temporally limited measurements, to estimate the tidal energy resources in the Magellan strait and evaluate the impacts of varying climatic conditions. The numerical model will also allow to predict the complementarity of tidal energy with other renewable resources, in the context of green hydrogen in the Strait of Magellan. This is the first study aimed at predicting the tidal energy resources in the Strait of Magellan, combining field observations and numerical models. Future work will focus on the interactions of physical and environmental processes that can help to promote a sustainable development of marine energies in the southern part of the continent.